UHMWPE/HDPE in-reactor blends, prepared by in situ polymerization: Synthetic aspects and characterization - A. E. Ferreira; M. L. Cerrada; E. Perez; V. Lorenzo; E. Valles; J. Ressia; H. Cramail; J. P. Lourenco; M. R. Ribeiro (eXPRESS Polymer Letters)
This work covers the synthesis and characterization of in-reactor Ultra-High Molecular Weight Polyethylene/High Density Polyethylene, UHMWPE/HDPE, blends by in situ polymerization in a single reactor, through dual catalyst immobilization. These blends are synthesized combining two different catalysts (one for each targeted molar mass) co-immobilized in mesoporous Santa Barbara Amorphous, SBA-15, particles. First, the ethylene polymerization behavior is investigated, under different polymerization conditions. Then, studies on the thermal, mechanical and rheological characteristics of the produced in-reactor blends are presented and their performance is compared and discussed in a comprehensive way. Moreover, the effect of different filler contents on the properties exhibited by the resulting materials is investigated. Results have shown that these in-reactor UHMWPE/HDPE blends exhibit a complex thermal, mechanical and rheological behavior, which depends mainly on the proportion between the two polymer components and on the amount of SBA-15.